Direct access colonoscopy: impact of intervention on time to colorectal cancer diagnosis and treatment in North West Tasmania. Issue 10 (9th October 2017) - Allen, Penny; Gately, Lucy; Banks, Patricia; Lee, Adrian A. Y. S.; Hamilton, Garry; Tan, Lavinia; Sim, Sheryl
Abstract: Background: Direct access colonoscopy (DAC) allows general practitioners to refer directly for colonoscopy, without specialist review. Research suggests DAC reduces times to diagnosis and treatment of colorectal cancer. However, there is no information about outcomes of DAC in Australia. Aim: To determine if DAC in North West Tasmania expedited colorectal diagnosis and treatment. Methods: Pre‐post intervention study evaluating time from referral to diagnosis and definitive treatment. Patient demographic characteristics, referral, colonoscopy and treatment information was retrieved from hospital records. Timelines were investigated in standard referrals (SR), emergency department/inpatient referrals and DAC using survival analysis. Results: Two hundred and six colorectal cancer cases were identified (117 SR, 26 DAC, 48 emergency department/inpatient and 15 unknown pathways). Median time to colonoscopy/diagnosis (DAC 6 weeks vs SR 7 weeks, P  = 0.55) or definitive treatment (surgery/chemoradiation) (DAC 8 weeks vs SR 9 weeks, P  = 0.81) was not significantly improved with DAC. Among SR only, time to diagnosis was 9 weeks pre‐intervention versus 5 weeks post‐intervention ( P  = 0.13), and time to treatment was 11 weeks pre‐intervention versus 6 weeks post‐intervention ( P  = 0.07). Conclusion: There was no statistically significant improvement in time to colorectal cancer diagnosis or treatment among patients referred through DAC compared to SR. There was a trend towards improved waiting times for SR concurrent with the introduction of the DAC pathway, indicating improvement of all referral processes. DAC may not be effective at expediting colorectal cancer diagnosis if it is not accompanied by strict referral guidelines. Larger evaluations of DAC are required in the Australian context.